Mircotheacing Sebagai Langkah Awal Calon Guru dalam Menguasai Keterampilan Dasar Mengajar di Kelas - Sr. Sipayung. R; Sihaloho S; Tarigan H; Sinurat T; Tarigan N; Girsang H; Manik R; Damanik W; Dongoran D; Sinaga M (Universitas 45 Surabaya, 2024)
Learning is not a simple process but a comprehensive, dynamic and complex process that brings together the components of learning in an integrated manner, such as, among others, learning objectives or competencies that must be achieved by students, materials that will become teaching materials for students, methods, media and sources, learning evaluations, students, teachers and other learning environments.The type of research used in this paper is a literature review study. To become a professional educator, prospective educators must undergo a micro-learning stage known as microteaching. In this paper, we will discuss the role of the microteaching course in preparing students to teach and develop skills from existing ones into new skills. Microtheacing includes some basic teaching skills that students must master before becoming a professional teacher. Therefore, microteaching is the first step for prospective teachers in gaining knowledge and learning about eight teaching skills in the classroom.